PENGARUH SIKAP KONSUMEN TERHADAP LOYALITAS MEREK SHAMPO SUNSILK PADA MAHASISWI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MULAWARMAN SAMARINDA - Jayanti Reike; Herning Indriastuti; Suharno Suharno (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
Jayanti Reike, 2018 The Influence of Consumer Attitudes on Brand Loyalty Sunsilk Shampoo (Case Study on Student of Economics and Business Faculty of Mulawarman University of Samarinda), under the guidance of Prof.Dr.Suharno, SE., MM and Mrs. Dr. Herning Indriastuti, SE., MM.                Aims to examine whether Consumer Attitudes have a positive and significant effect on Brand Loyalty Shampo Sunsilk.The independent variables in this study are cognitive, affective, and conative.While the dependent variable is Brand Loyalty.Research was conducted on Student Faculty of Economics and Business Mulawarman University of Samarinda, which consists of 150 respondents.               This study is quantitative.The data collection by kuisoner by testing consumer attitudes consisting of Cognitive, Affective, and conative attitudes with Brand Loyalty Data analysis using multiple linear regression.This study results in the variables of cognitive, affective , and Konatif owns a character uh that is positive and significant to Brand Loyalty.